Arthrocentesis Versus Pharmacological Therapy for the Management of Patients with Temporomandibular Joint Disc Displacement Disorders - Aneeza Ayyaz; Aqib Sohail; Fareed ud Din Ahmad Chishti; Ayesha Muhammad Rana; Zoya Aslam; Ali Ammar Hasan (Journal of University College of Medicine and Dentistry)
Objective: To compare the effectiveness of arthrocentesis versus pharmacological therapy in improving maximal mouth opening (MMO) in patients with temporomandibular joint (TMJ) disc displacement disorders.